2022
DOI: 10.1002/adsc.202200026
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Cycloisomerization of Enyne Diesters Derived From 2‐Propargyloxyarylaldehydes

Abstract: A catalytic cycloisomerization of enyne diesters derived from 2-propargyloxyarylaldehydes is described. The cycloisomerization, catalyzed by 10 mol% In(OTf) 3 , provides access to 2H-chromenes bearing diethyl 2-(hetero)arylidene malonates at 3-position. This enyne metathesis-type reaction is also useful for the synthesis of thia-, aza-and quinoline analogs of the 3-substituted 2H-chromenes. DDQ mediated oxidative CÀ N bond formation and further synthetic manipulation enables the conversion of 3-substituted 2H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…. 24 Purification by flash column chromatography on silica gel eluting with the petroleum ether/ethyl acetate mixture (95:05 to 90:10, v/v) afforded the title compound as a colorless solid; mp 103−105 °C; yield: 83% (0.233 g).…”
Section: -((3-(4-nitrophenyl)prop-2-yn-1-yl)oxy)benzaldehyde (1k)mentioning
confidence: 99%
“…. 24 Purification by flash column chromatography on silica gel eluting with the petroleum ether/ethyl acetate mixture (95:05 to 90:10, v/v) afforded the title compound as a colorless solid; mp 103−105 °C; yield: 83% (0.233 g).…”
Section: -((3-(4-nitrophenyl)prop-2-yn-1-yl)oxy)benzaldehyde (1k)mentioning
confidence: 99%
“…Recently, Novikov, Tomilov and co‐workers demonstrated a new concept of utilizing dialkyl β‐arylidenemalonates as 1,2‐zwitterionic synthons in the presence of stoichiometric amount of gallium halides for various useful synthetic transformations including the synthesis of indenes and lactones [25] . Inspired by these literature reports, our group recently carried out an intramolecular annulation reaction of enyne diesters derived from 2‐propargyloxyarylaldehydes bearing internal alkynes (having aryl/heteroaryl substituents) in the presence of catalytic amount metal salts containing non‐nucleophilic ligands (such as In(OTf) 3 ) and observed that the substrates undergo a formal [2+2]‐cycloaddition and concomitant cyclo‐reversion reaction [26] . The overall outcome was an enyne metathesis [27] type cycloisomerization reaction providing direct access to functionalized 2 H ‐chromenes, its aza‐ and thia‐analogues with diethyl β‐((hetero)aryl)arylidene malonate moiety pendented at 3‐position.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Inspired by these literature reports, our group recently carried out an intramolecular annulation reaction of enyne diesters derived from 2-propargyloxyarylaldehydes bearing internal alkynes (having aryl/ heteroaryl substituents) in the presence of catalytic amount metal salts containing non-nucleophilic ligands (such as In(OTf) 3 ) and observed that the substrates undergo a formal [2 + 2]-cycloaddition and concomitant cyclo-reversion reaction. [26] The overall outcome was an enyne metathesis [27] type cycloisomerization reaction providing direct access to functionalized 2Hchromenes, its aza-and thia-analogues with diethyl β-((hetero)aryl)arylidene malonate moiety pendented at 3-position. In this report we demonstrate that polycyclic (hetero)aromatic compounds and related systems bearing synthetically useful dialkyl β-(hetero)arylidene malonate moiety are obtained via In(OTf) 3 -catalyzed cycloisomerization reaction of enyne diesters derived from biaryls and related substrates (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…10 Furthermore, the In(OTf) 3 catalyzed reaction of arylidene malonates bearing an aryl alkyne moiety gave metathesis type products via [2 + 2] cycloaddition and cycloreversion. 11…”
Section: Introductionmentioning
confidence: 99%
“…10 Furthermore, the In(OTf ) 3 catalyzed reaction of arylidene malonates bearing an aryl alkyne moiety gave metathesis type products via [2 + 2] cycloaddition and cycloreversion. 11 In order to examine the generality of the Diels-Alder reaction of aryl alkynes and expand the utility of aryl alkynes as a donor component, the reactions of 3-aryl-2-propynylamides of electron-deficient α,β-alkenyl carboxylates have been investigated. In this work, potentially useful multicyclic and monocyclic pyrrolidine rings with various functional groups have been obtained chemoselectively (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%